Exploring Multimodal Texts in Education: A Genre Analysis of Digital Learning a Materials for EFL Students - Sarah Shabrina Fadhilah; Yogi Setia Samsi; Revina Pinkan Septiani (IKIP Siliwangi, 2026)
This study investigates the use of multimodal texts and genre-based pedagogy in fully digital learning materials for fifth-grade English as a Foreign Language (EFL) students. Using a qualitative descriptive approach, the study applies Genre Analysis and Multimodal Discourse Analysis to examine three Indonesian EFL digital learning units: Rock n Roll, Wild West, and Museum of the Future. Although multimodal approaches are recognized in language education, few studies examine their application across complete digital units. Focusing on three Indonesian EFL units: Rock n Roll, Wild West, and Museum of the Future, the research applies genre analysis and multimodal discourse analysis to explore how linguistic, visual, spatial, and interactive modes, together with instructional, descriptive, expository, procedural, and narrative genres, support grammar teaching, vocabulary building, and learner engagement. Findings indicate that these resources integrate multiple semiotic modes and genre variations to contextualize learning and enhance communicative competence. However, limitations such as inconsistent scaffolding, minimal vocabulary recycling, and the absence of embedded audiovisual content reduce alignment with multimedia learning principles. Recommendations are offered to improve digital material design through stronger multimodal integration, broader genre inclusion, and adaptive features for diverse learners.